Growth and bioaccumulation of cadmium, zinc, lead, copper in Dunaliella sp. isolated from Homa lagoon, eastern Aegean Sea - Kutlu, Banu; Mutlu, Ekrem (My University, 2017)
Present study consists the growth of cell and bioaccumulation capacity of Cadmium (Cd), Zinc (Zn), Lead (Pb), Copper (Cu) by Dunaliella sp. isolated from Homa Lagoon, Eastern Aegean, Turkey. Sterile medium f/2 was used for the cultivation. Growth rate, mean growth rate, relative growth rate and generation time of Dunaliella sp. were calculated for determining the growth of cell. In addition, optimum pH values were determined for each heavy metal. Our results pointed out that the optimum time for harvesting Dunaliella sp. was in 8 days. Uptake of heavy metals of Dunaliella sp. showed high tendency for zinc accumulation followed by copper, lead, and the lowest tendency was for cadmium. Highest bioaccumulation of Zn was determined to be 151.64 μg/L at 2.45 of pH under in situ conditions. pH had noticeably affected the bioaccumulation capacity of Dunaliella sp.
Keywords: Dunaliella sp.; Dunaliella sp; Heavy Metals; Bioaccumulation; Cell Growth; 6. Clean water